Comparison of ChatGPT and Internet Research for Clinical Research and Decision-Making in Occupational Medicine: Randomized Controlled Trial - Felix A Weuthen; Nelly Otte; Hanif Krabbe; Thomas Kraus; Julia Krabbe (JMIR Formative Research)
Abstract BackgroundArtificial intelligence is becoming a part of daily life and the medical field. Generative artificial intelligence models, such as GPT-4 and ChatGPT, are experiencing a surge in popularity due to their enhanced performance and reliability. However, the application of these models in specialized domains, such as occupational medicine, remains largely unexplored. ObjectiveThis study aims to assess the potential suitability of a generative large language model, such as ChatGPT, as a support tool for medical research and even clinical decisions in occupational medicine in Germany. MethodsIn this randomized controlled study, the usability of ChatGPT for medical research and clinical decision-making was investigated using a web application developed for this purpose. Eligibility criteria were being a physician or medical student. Participants (N=56) were asked to work on 3 cases of occupational lung diseases and answer case-related questions. They were allocated via coin weighted for proportions of physicians in each group into 2 groups. One group researched the cases using an integrated chat application similar to ChatGPT based on the latest GPT-4-Turbo model, while the other used their usual research methods, such as Google, Amboss, or DocCheck. The primary outcome was case performance based on correct answers, while secondary outcomes included changes in specific question accuracy and self-assessed occupational medicine expertise before and after case processing. Group assignment was not traditionally blinded, as the chat window indicated membership; participants only knew the study examined web-based research, not group specifics. ResultsParticipants of the ChatGPT group (n=27) showed better performance in specific research, for example, for potentially hazardous substances or activities (eg, case 1: ChatGPT group 2.5 hazardous substances that cause pleural changes versus 1.8 in a group with own research; PrPP ConclusionsChatGPT can be a useful tool for targeted medical research, even for rather specific questions in occupational medicine regarding occupational diseases. However, clinical decisions should currently only be supported and not made by the large language model. Future systems should be critically assessed, even if the initial results are promising.